Preparation of yarn by blending of etherified jute fibre with natural and synthetic fibre - Dr.Nurul (European Journal of Applied Sciences, 2022)
Yarns were prepared by blending the etherified jute fibre in different combinations with cotton, rayon, polyester and silk waste. A blend of 50:50 for each fibre component was prepared with 50% of the etherified jute fibre respectively and 30 tex yarns from each blend were produced using the ring spinning fame. The physical properties of these yarns were determined with respect to the same numbered yarns of cotton. The 50% of the etherified jute fibre in the blends produced yarns having tenacities between 10.9 to 11.9 (g/tex) which are very much comparable to tenacity 11.5 (g/tex) of the same numbered cotton yarns. The breaking elongation 6.2 to 6.4%, moduli between 181 to 184 (g/tex) and count strength product 1605 to 1638 of the yarns from etherified jute & cotton and etherified jute and rayon in the ratio of 50:50 were almost similar to the respective properties 6.6 %, 171(g/tex) and 1694 of the same numbered cotton yarn. The breaking elongation of yarns from etherified jute and polyester and etherified jute and silk was much higher between 12.4 to 12.7% which were due to highly extensible polyester and silk fibres in the combination.